Determinants of customer experience in e-services: the case of online universities - Izquierdo-Yusta, Alicia; Jimenez-Zarco, Ana; Martinez-Ruiz, Maria Pilar Maria Pilar; González-González, Ines (RBGN-Revista Brasileira de Gestao de negocios, 2021)
Purpose - The study analyzes the key drivers of consumer experience in e-services, with the particular goal of defining and quantifying the influence of website quality and university brand assessments on the experience of consumers who are students of a virtual university. Theoretical framework - To carry out the research we analyzed website quality, brand, and customer experience Design/methodology/approach - We carried out a statistical analysis using structural equation modeling of web-based questionnaires collected from 306 postgraduate students of a virtual university. Findings - Our research reveals that the university's brand is the most influential factor. In contrast, the influence exerted by the web environment is lower. Of the three website dimensions, the quality of the system exerts the greatest influence, followed by relationship quality, which is moderated by the role of university staff. Research, practical, and social implications - We propose that the quality of a virtual classroom (quality of the system, quality of information, and service quality), together with students' individual assessments of the brand, determine the students' experience as consumers of this service. The brand assessment is the most important factor.
Keywords: student experience; website quality; brand assessment; virtual learning environment; virtual universities; WOS(2)